MTFR2 Promotes the Proliferation, Migration, and Invasion of Oral Squamous Carcinoma by Switching OXPHOS to Glycolysis - Wang, Wei; Xiong, Meihua; Jiang, Lin; Chen, Zean; Shao, Yisen (Frontiers in Oncology, 2020)
MTFR2 is an oncogene involved in the progression of cancer, its' potential mechanism in oral squamous carcinoma remains unknown. The aim of this study was to uncover the bio-function and the mechanism of MTFR2 in the progression of oral squamous carcinoma. We scanned TCGA database to identify MTFR2 as dysregulated genes. qRT-PCR and Western blotting assays were applied to detect the expression pattern of MTFR2 in oral squamous carcinoma. We next established stable MTFR2-overexpressing and MTFR2 knocking down cell lines. A series of experiments were applied and the results indicated that MTFR2 was upregulated in cancer tissue and negatively correlated with the overall survival (OS) of patients in both the TCGA database and our inhouse database. Following experiments showed that MTFR2 promotes proliferation, migration and invasion in an oral squamous carcinoma cell line by switching OXPHOS to glycolysis.